Optimalisasi Pembelajaran: Panduan Digitalisasi Bahan Ajar bagi Guru di SDN 03 Situjuah Banda Dalam - Gina Khairunnisa (Universitas 45 Surabaya, 2024)
Education is a field that continues to develop along with technological developments. One effort to optimize learning is by digitizing teaching materials. Learning in the digital era requires teachers to optimize the use of technology in compiling teaching materials. This article aims to provide a guide to digitizing teaching materials for teachers at SDN 03 Situjuah Banda Dalam, with a focus on optimizing learning. This research provides a guide to digitizing teaching materials for teachers at SDN 03 Situjuah Banda Dalam. The research method used is qualitative research, with data collection techniques through literature study, observation, and interviews with teachers who have experience in digitizing teaching materials. Apart from qualitative research methods, the methods also used are literature studies and field observations to evaluate teacher needs and learning conditions in the school. The results of this research are a step-by-step guide regarding the process of digitizing teaching materials, as well as strategies for optimizing learning using digital teaching materials and providing practical guidance in utilizing digital technology to improve the quality of learning at SDN 03 Situjuah Banda Dalam. It is hoped that this guide can be a reference for teachers at SDN 03 Situjuah Banda Dalam and other schools in facing the era of digitalization of education.